Model reference adaptive neuro-controller with on-line parameter estimation - Siti Maryam, Sharun; Mohd Yusoff, Mashor, Prof. Dr.; Norhayati, Mohd Noor; Wan Nurhadani; Sazali, Yaacob, Prof. Dr.; Muhyi, Yaakob (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.